ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI DIVIDEN KAS - Mutia, Anisa; Dillak, Vaya Juliana (Aksara Public, 2018)
This study aims to explain how Earning per share (EPS), Quick Ratio, Operating Cash Flow, Debt to Equity Ratio, Company Size and Cash Dividend and to find out whether there are simultaneous and partial effects between Earning per Share, Quick Ratio, Cash Flow Operations, Debt to Equity Ratio and Company Size to Cash Dividends in all manufacturing companies registered at Butsa Efek Indonesia for the period 2013-2016. This study uses quantitative methods. The sampling technique used was purposive sampling technique. The sample in this study was 92 samples in 4 years. The analysis technique used is multiple linear regression analysis using SPSS version 20. Based on the results of the study, variables Earning per Share (EPS), Quick Ratio, Operating Cash Flow, Debt to Equity Ratio, and Company Size simultaneously have a significant effect on Cash Dividend. Partially, the variable Earning per Share (EPS) and Company Size have a positive effect on cash dividends, the variable Debt to Equity Ratio has a negative effect on Cash Dividends. While the Quick Ratio variable and operating cash flow variables do not affect the Cash Dividend.